Prey: Cyberbullying’s Consequences Toward Victim’s Mental Health and His Social Life - Jeffry Kurniawan (Institute of Research and Community Outreach - Petra Christian University, 2021)
This screenplay project focuses on cyberbullying's impacts on its victims, both mentally and physically. The goal is to shed light into this action of crime that is often overlooked, to make a better cyberspace environment, and to raise awareness to the public, especially cyberbullying perpetrators, to stop what they are doing. To do so, this creative thesis uses the cyberbullying concept that points out how cyberspace bullying can trigger paranoia and depression among many other mental disorders. The work is based on theories on paranoia, depression and cyberbullying itself. From the screenplay, it is shown how the main characters got cyberbullied, and later went from a healthy, hardworking, resilient man to a mentally broken human being as a consequence. By understanding the impact the act of cyberbullying can have on a person’s life, cyberspace users can be more responsible and refrain themselves from the act of cyberbullying.Keywords: Cyberbully, Screenplay, Depression, Paranoia, Psychological Thriller.